Evaluation of urban trees selection for sustainable parking lots - Dayang Zahidah, binti Abg Mohamad Othman (Universiti Malaysia Sarawak (UNIMAS), 2014)
The increments of urban population have led to an increased need of facility. One of the facilities required is parking lots to meet the increased use of vehicles. The larger car park surface has led to an increase in temperature in the city making it hotter. Therefore, tree planting is necessary to achieve the sustainable environment. However, to achieve a sustainable level, only suitable trees can be planted in the parking lots. Through the results of the study, selection of species like Pongamia pinnata is very suitable for planting to get the cooling and shading effect in the parking lots. Thus the pollution level will be decreased and the impacts of parking lots will be reduced. Besides the types of trees, sufficient planting space both below and above ground is to be taken into account because it affects the rate of tree growth and surface parking situation event if the right species of trees were planted.